ABUSE OF THE OFFICIAL POSITION BY THE CUSTOMS AUTHORITIES OF THE REPUBLIC OF POLAND (1920–1927-I RR.) - KLISH, Andrii; MOSKALIUK, Mykola (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Abstract. The article examines the abuse of official position by the customs authorities of the Republic of Poland in 1920–1927. The outlined problem is practically not covered in Ukrainian historical science, therefore it required a holistic and systematic analysis. The formation of the customs authorities of the Republic of Poland took place in the difficult conditions of the restoration of its statehood. It is quite natural that this was reflected in the organization of customs authorities. Such negative manifestations in the activities of customs structures, such as: abuse of official position, which manifested itself in the reduction of revenues to the state budget, additional and unfounded tax payments, the absence of publicly available information on the terms of validity of preferential conditions for the export and import of goods and cargo, “different readings” regulatory and legal documentation, etc., were the result, on the one hand, of the lack of sufficiently qualified professional personnel at the initial stage of formation, their low financial status, and on the other hand, weak control by the inspectorates of the customs guard, the «Directorate of Customs in Lviv» and the Customs Department of the Ministry of Finance. Taking into account the massive manifestations of abuse of official position by the customs authorities of the Republic of Poland in the specified period, the authorities tried to radically change the situation exclusively with administrative and disciplinary sanctions, but during the outlined period it was not possible to significantly improve it. The specific actions of the inspectorates of the customs guard, the «Directorate of Customs in Lviv» and the Department of Customs of the Ministry of Finance in overcoming abuses of official position were usually based on the inspection of official documents, efforts to bring the guilty to administrative responsibility. As evidenced by the analysis of archival records cases, such cases were not mass, but individual facts. The problem was that it was quite difficult for both individuals and legal entities to prove the abuse of their official position by the customs authorities of the Republic of Poland, since the officials used a powerful bureaucratic apparatus, a significant number of instruction letters, orders, tariff grids regarding the amounts of taxes on exports or imports of goods or cargo. Only those enterprises or entrepreneurs who hired professional lawyers who proved the illegality of the actions of the customs authorities in a court of law were able to partially solve the looming problem. In our opinion, this is primarily related to the amount of additional charges by customs authorities for tax payment, when the cost of lawyers' services did not exceed it.